Chromosome Division in Early Embryos-Is Everything under Control? And Is the Cell Size Important? - Horakova, Adela; Konecna, Marketa; Anger, Martin (International journal of molecular sciences, 2024)
Chromosome segregation in female germ cells and early embryonic blastomeres is known to be highly prone to errors. The resulting aneuploidy is therefore the most frequent cause of termination of early development and embryo loss in mammals. And in specific cases, when the aneuploidy is actually compatible with embryonic and fetal development, it leads to severe developmental disorders. The main surveillance mechanism, which is essential for the fidelity of chromosome segregation, is the Spindle Assembly Checkpoint (SAC). And although all eukaryotic cells carry genes required for SAC, it is not clear whether this pathway is active in all cell types, including blastomeres of early embryos. In this review, we will summarize and discuss the recent progress in our understanding of the mechanisms controlling chromosome segregation and how they might work in embryos and mammalian embryos in particular. Our conclusion from the current literature is that the early mammalian embryos show limited capabilities to react to chromosome segregation defects, which might, at least partially, explain the widespread problem of aneuploidy during the early development in mammals.
Keywords: Animals; Mammals; segregation errors; Female; segregace chromozomů; aneuploidie; ženské pohlaví; Cell Size; lidé; embryo; spindle; CDK1; spindle assembly checkpoint; cell size; Chromosomes; savci; velikost buňky; Embryonic Development; aneuploidy; chromosome division; zvířata; embryonální vývoj; Aneuploidy; Chromosome Segregation; chromozomy; Humans